The Influence of Credit Risk and Liquidity with Guarantee Interest Rate as a Moderator on the Financial Performance of Conventional and Islamic Rural Banks (BPR and BPRS) - Rachman, Arief; Putra Pamungkas (Journal of Finance and Islamic Banking, 2024)
This study aims to evaluate the financial performance (profitability), credit risk, and liquidity of BPR and BPRS before and during the pandemic. The study focuses on analyzing the impact of credit risk and liquidity on profitability and the moderating effect of the guarantee interest rate on liquidity in relation to the financial performance of BPR and BPRS. Design/methodology/approach: A total sample of 1,349 BPR and 153 BPRS across Indonesia was analyzed using Stata software. The research employed quantitative methods to test the proposed hypotheses regarding the relationships between credit risk, liquidity, and profitability, while assessing the moderating role of the guarantee interest rate. Research Findings: The findings show that NPL/NPF significantly affects the financial performance (ROA) of BPR and BPRS, with an increase in NPL/NPF negatively impacting profitability. Additionally, the guarantee interest rate strengthens the positive relationship between LDR/FDR and ROA, indicating that higher interest rates improve fund management and financial performance. Theoretical Contribution/Originality: This study contributes to the literature by highlighting the significant role of credit risk management and the importance of interest rate moderation in enhancing the financial stability and profitability of BPR and BPRS. It also emphasizes the differences in risk management approaches between BPR and BPRS, especially during economic downturns like the pandemic.